Environmental impact assessment handbook a practical guide for planners, developers and communities - Carroll, Barbara, 1950- (Thomas Telford, 2009)
The authors employ their extensive practical experience to cover every step and associated studies needed to undertake an EIA and to produce a successful environmental statement. This second edition is fully updated and expanded to include a new chapter on Strategic Environmental Assessment (SEA).